Actitudes hacia el catalán del futuro profesorado aragonés de Educación Primaria - Campos, I.O. (2015)
Catalan is one of the Aragonese regional languages. In spite of its introduction as a school subject three decades ago in some Eastern Aragonese schools, Catalan has no presence in the teacher training degree at the University of Zaragoza. Considering the threatened status of the Aragonese regional languages and the influence of school context, and particularly teachers, on the pupils¿ linguistic attitudes, it seems necessary to know what the linguistic attitudes of future Aragonese teachers towards their regional languages are. The present study reveals very unfavorable attitudes towards Catalan by first and fourth year Aragonese students of the degree in primary education teaching.